Uranium series dating reveals a long sequence of rock art at Altamira Cave (Santillana del Mar, Cantabria) - García-Diez, M. (2018)
The rock art in Altamira Cave was the first ensemble of Palaeolithic parietal art to be identified scientifically (Sautuola, 1880). Due to the great thematic, technical and stylistic variety of the art in the cave, which constitutes one of the most complete Palaeolithic art ensembles, Altamira was listed as World Heritage by UNESCO in 1985. Uranium-series dating has recently been applied to figures on the decorated ceiling in the cave. Several motifs are partly covered by thin layers of calcite precipitates, whose formation process is datable by this method. The results provide the date when the calcite formed, which gives a minimum age for the underlying depictions. These results confirm that the parietal art at Altamira was produced during a prolonged period of time, at least 20,000 years (between 35,000 and 15,200 years ago), and that part of the ensemble corresponds to the Aurignacian period.